2013
DOI: 10.1111/ejss.12073
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emissions from biochar in soil: role of clay, microorganisms and carbonates

Abstract: Summary The stability of biochar in soil is of importance if it is to be used for carbon sequestration and long‐term improvement of soil properties. It is well known that a significant fraction of biochar is highly stable in soil, but carbon dioxide (CO2) is also released immediately after application. This study investigated the nature of the early release of CO2 and the degree to which stabilizing mechanisms protect biochar from microbial attack. Incubations of 14C‐labelled biochar produced at different temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 34 publications
(52 reference statements)
2
62
1
Order By: Relevance
“…We also identified calcite by XRD in the biochar (Fig. 5, pre-acid treatment only) which is consistent with previous research (Yuan et al 2011b;Bruun et al 2014). It is likely protons (H + ) in the acid drainage dissolve solid phase carbonate/calcite in the biochar to form dissolved alkalinity/HCO 3 − and Ca 2+ in the leachate water (Fig.…”
Section: Potential Treatment Mechanismssupporting
confidence: 90%
“…We also identified calcite by XRD in the biochar (Fig. 5, pre-acid treatment only) which is consistent with previous research (Yuan et al 2011b;Bruun et al 2014). It is likely protons (H + ) in the acid drainage dissolve solid phase carbonate/calcite in the biochar to form dissolved alkalinity/HCO 3 − and Ca 2+ in the leachate water (Fig.…”
Section: Potential Treatment Mechanismssupporting
confidence: 90%
“…Other studies have examined the interactive priming effects (i.e., stimulation or suppression of C mineralization) of LOM and recalcitrant C applied to soil simultaneously (Hamer et al 2004;Liang et al 2010;Keith et al 2011;Rogovska et al 2011;Zavalloni et al 2011). Results were contradictory and may relate to the different soil characteristics, variable biochar feedstock, production conditions, and study durations used in these studies (Zimmerman et al 2011;Bruun et al 2014). For example, reported no or small mineralization of pecan-shell biochar (7008C) in the presence of fresh LOM (switchgrass residue), whereas the presence of the biochar enhanced the mineralization of the added fresh LOM.…”
Section: Properties Of Soils and Organic Amendmentsmentioning
confidence: 99%
“…3 Dynamics of soil pH of all treatments during a period of 68-day, in which each value represents the mean of three replicates with the standard error shown by the vertical bars Each value is the mean of three replicates with the standard deviation, and values marked with the same letters in soil-PB or soil-PT treatment are not significantly different (P>0.05) a PBV soil+PB (ventilated incubation), PBS soil+PB (sealed incubation), PTV soil+PT (ventilated incubation), PTS soil+PT (sealed incubation), CKV soil only (ventilated incubation), CKS soil only (sealed incubation) b Δ pH means pH increment in soil-biochar treatments compared to the controls incubated under the same conditions biochars, especially carbonate in PB, can ameliorate soil acidity to some extent through a neutralization reaction (Table 2 and Figs. 1 and 2) (Bruun et al 2014); and (e) the large surface area and porous property of biochar immobilize ammonium N and then inhibit nitrification (Nelissen et al 2012;Pocknee and Sumner 1997), leading to soil acidity amelioration. This is supported by the negative correlation between pH and nitrate N (r=−0.742, P<0.01, n=18), suggesting that PB and PT could be used as an agent to apply to soils with fertilizer, which then plays a similar role to that of a nitrification inhibitor in soil acidity amendment through nitrification suppression (Mao et al 2010).…”
Section: Soil Acidity Amendment Using Biocharmentioning
confidence: 99%
“…In addition, clay content has an important role in maintaining soil structure, CEC, and other local environmental condition in soils (Bruun et al 2014). A previous study has reported that incubation condition (ventilated and sealed) had few effects on acidification amendment in clayey soils in hilly red soil region of southern China (Zhao et al 2015a).…”
Section: Introductionmentioning
confidence: 98%